Application of Energy-Saving Airflow Technology for Finishing and Strengthening Processing of Thin-Walled Cylindrical Parts - Fayzimatov Shukhrat Numanovich (Mathematical Statistician and Engineering Applications, 2022)
This article examines the results of research on the application of the energy of swirling air flows in the finishing and strengthening processing of thin-walled cylindrical parts. The main goal of the research is the point contact of the ball with the treated surface, which provides high specific pressures on the walls of the part at low loads, the simplicity of the design and the relatively low cost of the tool causes the use of ball rolling for finishing and hardening processing of thin-walled and low-rigid parts with a large ratio of length to the outer diameter and wall thickness. It is hoped that after results obtained from the research will ensure significant advantages such as developing the concept of aerodynamic effect-based production, aerodynamic action of finishing and strengthening processing of thin-walled cylindrical parts, obtaining surface roughness in high accuracy.